Petroleum Revenue Management Workshop - World Bank (World Bank, Washington, DC, 2014)
The Oil, Gas, Mining and Chemicals Department, and the World Bank/UNDP Energy Sector Management Assistance Programme (ESMAP) hosted a workshop on Petroleum Revenue Management on October 23-24, 2002 in Washington, D.C. The workshop brought together petroleum industry, civil society, developmental agencies, academics and country representatives to discuss experiences, challenging operational problems faced, and emerging best practices with respect to petroleum revenue management. The report contains the proceedings of the conference. It includes the introductory remarks, the sessions on revenue collection, management, and distribution, and the roundtable and closing discussion.